Air quality and the risk of out-of-hospital cardiac arrest in Singapore (PAROS): a time series analysis. (November 2022) - Ho, Andrew Fu Wah; Ho, Jamie S Y; Tan, Benjamin Yong-Qiang; Saffari, Seyed Ehsan; Yeo, Jun Wei; Sia, Ching-Hui; Wang, Meng; Aik, Joel; Zheng, Huili; Morgan, Geoffrey; Tam, Wilson Wai San; Seow, Wei Jie; et al.
Summary: Background: Previous studies have reported positive associations between out-of-hospital cardiac arrest (OHCA) and air pollutant concentrations, but there are inconsistencies across studies. We aimed to investigate the association between pollutant concentrations and the risk of OHCA in Singapore. Methods: We did a time series analysis of all cases of OHCA in Singapore reported between July 1, 2010, and Dec 31, 2018, to the Pan-Asian Resuscitation Outcomes Study (PAROS), a prospective, population-based registry. Using multivariable fractional polynomial modelling, we investigated the immediate (day 0) and lagged (up to 5 days after exposure) association between 10 μg/m 3 increases in concentrations of particulate matter with a diameter of 2·5 μm or smaller (PM2·5 ), particulate matter with a diameter of 10 μm or smaller (PM10 ), ozone (O3 ), nitrogen dioxide (NO2 ), and sulphur dioxide (SO2 ) and 1 mg/m 3 increase in carbon monoxide (CO) and relative risk (RR) of OHCA. Findings: We extracted data for 18 131 cases of OHCA. The median age of this cohort of cases was 65 years (IQR 56–80), 6484 (35·8%) were female, 11 647 (64·2%) were male, 12 270 (67·7%) were Chinese, 2873 (15·8%) were Malay, and 2010 (11·1%) were Indian. Every 10 μg/m 3 increase in PM2·5 was associated with increased risk of OHCA (RR 1·022 [95% 1·002–1·043]) over the next 2 days, which decreased over the subsequent 3 days (3–5 days after exposure; 0·976 [0·955–0·998]). For PM10, O3, NO2, and SO2, we did not observe any associations between increased concentration and risk of OHCA on day 0 or cumulative risk over time (ie, at 0–1 days, 0–2 days, 0–3 days, 0–4 days, 0–5 days, and 3–5 days after exposure). For CO, we observed a cumulative decreased risk of OHCA across 0–5 days after exposure (0·876 [0·770–0·997]) and at days 3–5 after exposure (0·810 [0·690–0·949]). We observed effect modification of the association between increasing PM2·5 concentration and OHCA 0–2 days after exposure by cardiac arrest rhythm (non-shockable 1·027 [1·004–1·050] vs shockable 1·002 [0·956–1·051]) and location of OHCA (at home: 1·033 [1·008–1·057] vs not at home 0·955 [0·957–1·035]). In hypothetical modelling, the number of OHCA events associated with PM2·5 could be reduced by 8% with a 1 μg/m 3 decrease in PM2·5 concentrations and by 30% with a 3 μg/m 3 decrease in PM2·5 concentrations. Interpretation: Increases in PM2·5 concentration were associated with an initial increased risk of OHCA and a subsequent reduced risk from 3–5 days after exposure, suggesting a short-term harvesting effect. A decrease in PM2·5 concentrations could reduce population demand for emergency health services. Funding: National Medical Research Council, Singapore, under the Clinician Scientist Award, Singapore and the Singapore Translational Research Investigator Award (MOH-000982-01).